Upaya Peningkatan Perilaku Caring Perawat dalam Praktik Keperawatan di Unit Rawat Inap - Maria Faleria Yung; Reni Yuli Astutik (Yayasan Inspirasi El Burhani, 2026)
Introduction: Effective communication and caring behavior are essential components of nursing services that influence patient comfort, satisfaction, and quality of care. Preliminary assessments at the Interna Women’s Inpatient Unit of Hospital Nacional Guido Valadares indicated suboptimal nurse–patient communication, reflected in patient complaints and limited understanding of therapeutic communication principles among nurses. Objective: The purpose of this community service was to improve nurses’ knowledge and practice of effective communication and caring behavior in inpatient nursing care. Method: This public service was conducted using a descriptive–intervention approach involving education, training, and coaching for nurses. Problem identification and prioritization were performed using fishbone, USG (Urgency, Seriousness, Growth), and SWOT analyses. Evaluation was carried out using a pre-test and post-test design and direct observation of nursing practices. Result: The results showed an improvement in nurses’ knowledge scores from 72% at pre-test to 88% at post-test, indicating a 16% increase after the intervention. Observations also revealed better implementation of structured communication, self-introduction, clear explanation of procedures, and more empathetic nurse–patient interactions. Conclusion: The community service intervention effectively improved nurses’ communication knowledge and caring behavior, supporting the enhancement of nursing service quality and patient-centered care.